STATISTICAL METHODS OF DISCRIMINATED ECONOMIC ACTIVITY IN MACROECONOMIC INDICATORS - Irismatov Humoyunmirza Fahritdin Oglu (Journal Park Publishing, 2022)
This article examines the factors influencing the sustainable economic growth of our country. The share of the regions in the country's GDP was analyzed and appropriate conclusions were made. Also, based on the opinions of economists, authorship of some economic terms is given. It was recommended to use some economic terms in determining the macroeconomic stability of our country.
Keywords: gross domestic product, economic growth, macroeconomic stability, gross regional product